I giuristi che scrivono lettere: questioni di forme e di contenuti, attraverso gli epistularum libri di Proculo - Pellecchi, Luigi (Tesserae iuris, 2024)
Starting with an overview of the Roman lawyers as epistolographers, the study examines the nature of Proculus’ Epistularum libri, taking as a main reference point the treatment given by the compilers of the Digest to this letter collection, when presenting its excerpta in Justinian's anthology.